Tropical marine fish from Celukan Bawang Port, Buleleng, Bali, Indonesia - Aulia Rizkyanti (EDP Sciences, 2021)
Celukan Bawang port is located in Buleleng Regency, Bali, Indonesia. The area of Celukan Bawang Port has a coral reef ecosystem that is very rarely found in Indonesian ports. The coral reef has an important role for coral reef fish as their habitat. This study aims to conduct coral reef fish in the Celukan Bawang port area. A survey was conducted by using UVC (Underwater Visual Census) method at four (4) stations in October 2019. The coral-reef fish family identified in this research consisted of 853 individuals belonging to 14 families and 34 species. The dominant family were Pomacentridae (63.53%), Labridae (25.21%), Achanthuridae (2.70%), Chaetodontidae (1.17%), and Ptereleotrididae (1.17%). The most abundant species were Dascyllus trimaculatus (2270 ind/ha), Halichoeres prosopeion (1550 ind/ha), and Pomacentrus coelestis (95 ind/ha). Shannon-Wiener diversity index value was 2.414, and there were no dominant species observed.